Public Perception of Money Politics in the 2019 Elections (Case Study of the Simultaneous Elections in Penukal Abab Lematang Ilir Regency) - Aprianto, Lois (Program Studi Politik Islam Universitas Islam Negeri Raden Fatah Palembang, 2023)
This research is entitled Public Perceptions of Money Politics in the 2019 Election (Case Study of Simultaneous Elections in 2019 in Penukal Abab Lematang Ilir Regency). Money politics is politics by giving something to voters with the aim of bribing them to vote for certain candidates at the time of election. Through money politics, political support is given on consideration of money and other economic resources received by certain political actors. This study uses qualitative research methods and the primary data in this study are derived from respondents/informants who were studied by conducting direct observations and interviews, while the secondary data were books, journals, documentation, literature related to the problems studied, and information obtained from the community involved in the research problem. The research technique of collecting data is based on the results of observations, documentation, and interviews. The data analysis technique uses qualitative data, namely data reduction, data presentation and drawing verification conclusions. The results of this thesis research indicate that there are still many people in Penukal Abab Lematang Ilir district who support the existence of money politics due to economic limitations and lack of curiosity about the impact of money politics. As for the factors that cause money politics in the community of Penukal Abab Lematang Ilir district in addition to economic limitations and lack of education about money politics, namely cultural or traditional factors. The money politics that occurred in the Penukal Abab Lematang Ilir district has become a culture that is difficult to get rid of, because the people in the Penukal Abab Lematang Ilir district are no stranger to money politics and consider money politics as an additional livelihood. Because in every general election, candidates for election contestants usually practice money politics by going through black campaigns, dawn attacks and giving promises when the candidates for election contestants are elected.